Hindbrain Herniation and Banana and Lemon Sign After Open Fetal Myelomeningocele Repair – When Do These Signs Disappear and is Shunting Predictable? - Vonzun, Ladina; Winder, Franziska Maria; Meuli, Martin; Moehrlen, Ueli; Mazzone, Luca; Kraehenmann, Franziska; Huesler, Margaret; Zimmermann, Roland; Ochsenbein-Kölble, Nicole (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose The aim was to describe the sonographic follow-up of hindbrain herniation (HH), the banana and lemon sign after fetal myelomeningocele (fMMC) repair, and the time of disappearance of these signs after the intervention, and to investigate any predictive value for the necessity of shunting during the infant’s first year of life. Additionally, the sonographic evolution of the transcerebellar diameter (TCD) before and after fetal intervention was assessed.Patients and Methods The first 50 patients that underwent fMMC repair at Zurich Center for Fetal Diagnosis and Therapy (www.swissfetus.ch) were included in this study. Sonographic scans performed weekly after fMMC repair focusing on HH and banana and lemon signs were analyzed and compared between the shunted and the non-shunted group. ROC curves were generated for the time intervals of resolution of the signs in order to show their predictive accuracy for the need for shunting until 1 year of age.Results HH resolved in 48 fetuses (96 %) before delivery. The sonographic disappearance of HH within the first two weeks after fMMC repair was associated with a significantly lower incidence of shunt placement (OR 0.19; 95 % CI 0.4–0.9) during the first year of life (p = 0.03). All fetuses with persistent HH before delivery received a shunt. TCD growth was observed in all fetuses.Conclusion The reversibility of HH within two weeks after fMMC repair is associated with an 80 % lower incidence of shunt placement during the infant’s first year of life. Moreover, it allows the cerebellum to grow and to normalize its configuration.
Keywords: myelomeningozele; fetal surgery; hindbrain herniation; banana sign; lemon sign